PENGARUH PROMOSI DI INSTAGRAM DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN NASI PENGGODA SECARA ONLINE MELALUI OJEK ONLINE (OJOL) PADA MASA KARANTINA COVID-19 DI KOTA PONTIANAK - Muliani Muliani; Faradina Inda Wardhani (STIE 'INDONESIA' Pontianak, 2020)
The purpose of this research was to investigate the direct influence of promotion and service quality on purchase decision to order Nasi Penggoda via Ojek Online (Ojol) during the Covid-19 quarantine period in Pontianak. The research method was carried out causally by measuring the strength of the relationship between two or more variables. Through the distribution of interviews and questionnaires (Google Form),a total of 85 respondents were randomly selected for data collection. Multiple regression was used when conductiong data analysis from the said responses. The results of this research carried out, the hypothesis was clearly accepted. It proved that both promotion (X1) and service quality (X2) influenced simultaneously and partially to purchase decision on ordering Nasi Penggoda through Ojek Online (Ojol). On the other hand, partial research variables showed that service quality dominates more than promotion on the making of purchase decision.